Effect of Futures Trading on Sectoral Index Volatility - Dr. Amit Kumar Nag, Rahul S Joshi (International Journal of Advanced Science and Technology, 2020)
The Stock Exchange of Thailand (SET), based in Bangkok, has a market capitalization of 553.32 US Dollars and consist of 8 sectors. This study tests the impact of US Dollar futures and SET 50 Index futures on 3 major sectoral return volatilities. The sectors chosen are Service, Resource, and Financial which have the highest market capitalization. The relationship was investigated using 8 independent variables and 1 dependent variable using numerous methods including Unit Root Test, ARMA Model, and GARCH Model. This paper uses daily-time series data from June 2015 to April 2018. The results indicate that SET 50 Index Future Return Volatility has positive relationship with both the Service and Financial Sectors, SET 50 Trade Volume Volatility has a negative relationship with the Resource Sector and a positive relationship with the Financial Sector, and US Dollar Future Return has a positive relationship with all 3 sectors. The results show that investors need to pay attention to the expectation of future price of US Dollar, stock volatility, and SET 50 Trade volume. The period studied is only 3 years, therefore in order to have a better understanding of the relationships it is advised to use a longer period of time. It is also recommended to study the relationship using all 8 sectors and include more futures such as Gold.